The Gulf Crisis : implications for the environment - Archer, L (Oxford Institute for Energy Studies, 1990)
The Gulf crisis has thrown into sharp relief matters of key concern to national, regional and global security. It has refocused political attention and jerked nations out of an earlier complacency regarding such varied but key issues as the Palestinian question, energy security and the development process. It occurs in a new global context of changed East-West relations, and historic developments in the Soviet Union and Eastern Europe. With political will, it could be the catalyst for accelerated action on another issue of global concern: the environment.